1, 050 years of Hurricane Strikes on Long Island in The Bahamas. Issue 3 (15th March 2021) - Wallace, E. J.; Donnelly, J. P.; van Hengstum, P. J.; Winkler, T. S.; McKeon, K.; MacDonald, D.; d'Entremont, N. E.; Sullivan, R. M.; Woodruff, J. D.; Hawkes, A. D.; Maio, C.
Abstract: Sedimentary records of past hurricane activity indicate centennial‐scale periods over the past millennium with elevated hurricane activity. The search for the underlying mechanism behind these active hurricane periods is confounded by regional variations in their timing. Here, we present a new high resolution paleohurricane record from The Bahamas with a synthesis of published North Atlantic records over the past millennium. We reconstruct hurricane strikes over the past 1, 050 years in sediment cores from a blue hole on Long Island in The Bahamas. Coarse‐grained deposits in these cores date to the close passage of seven hurricanes over the historical interval. We find that the intensity and angle of approach of these historical storms plays an important role in inducing storm surge near the site. Our new record indicates four active hurricane periods on Long Island that conflict with published records on neighboring islands (Andros and Abaco Island). We demonstrate these three islands do not sample the same storms despite their proximity, and we compile these reconstructions together to create the first regional compilation of annually resolved paleohurricane records in The Bahamas. Integrating our Bahamian compilation with compiled records from the U.S. coastline indicates basin‐wide increased storminess during the Medieval Warm Period. Afterward, the hurricane patterns in our Bahamian compilation match those reconstructed along the U.S. East Coast but not in the northeastern Gulf of Mexico. This disconnect may result from shifts in local environmental conditions in the North Atlantic or shifts in hurricane populations from straight‐moving to recurving storms over the past millennium. Key Points: A reconstruction of past millennium hurricane activity from Long Island in The Bahamas conflicts with records from neighboring islands Storm properties, local hydrodynamics, and the depositional environment are important for storm deposition at a blue hole site Compilations of Atlantic paleohurricane records indicate century‐scale shifts in regional storm population over the past 1, 000 years